Pengenalan Huruf Hijaiyah Melalui Metode Bernyanyi dengan Menggunakan Media Flash Card pada Anak Usia 4-5 Tahun di Tempat Pendidikan Al-Qur’an (TPA) Babussalam Desa Sabuk Empat Lampung Utara Tahun Ajaran 2024 - Anisa Fitriana; Lidya Serli; Meli Yudestia Pratiwi; Riyadi Jaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The work program planned to be implemented in Sabuk Empat Village includes: Teaching good manners and akhlakul karimah, introducing hijaiyah letters using Flash Card media, teaching Arabic vocabulary, teaching Arabic reading and writing, teaching fiqh, du'a-do' a daily, and short surahs. The work program carried out at the PKM STAI Ibnu Rushd 2024 activities is running smoothly as it should. PKM students have had a positive impact on the children of TPA Babussalam. Based on the results of activities, observations and implementation, the PKM program has been planned, prepared and implemented.